Resistance to hydroxyurea in Aspergillus nidulans by gene mutation and by putative gene amplification. - J. A. Roper; D. J. Scanlon (Fungal Genetics Reports, 1988)
Resistance to hydroxyurea in Aspergillus nidulans by gene mutation and by putative gene amplification.